The efficiency and effectiveness of training for CM Faculty an investigation and analysis - Beatisula, Aisa Ji D.; Dago-ob, Melissa C.; Montenejo, Ana Rose N.; Saril, Jan Anthony G.; Ticao, Marion G. (1997.)
In a rapid growing society, there is a need for people to have the necessary skills and knowledge which would enable them to cope with the demands of the times. Thus, it can be said that trainings are essentials for the growth and development of an organization and society. Many schoalrs like Martirez, Rebore, Michalak and laird have expounded the nature, processes and necessity of trainings. This study, entitled "The Efficiency and Effectiveness of Trainings for CM Faculty: An investigation and analysis focuses on whether the trainings given to the educators of the students were efficiently or effectively provided. The objectives of this study is to identify the trainings provided to the faculty; to ascertain whether these trainings have been efficient and effective; and to recommend actions which would further improve this line of work. This has been through the use of descriptive research method. The primary tool used in the study is the survey questionnaire handed out to the faculty members and the data was treated with the use of percentage classifications. The respondents of this study are regular teachers of the College of Management who have been teaching in the college for three years or more. This would also include those who are holding administrative positions in the college. With the use of lottery technique of random sampling, seventeen (17) respondents were surveyed, eleven (11) of whom come from the Department of Management while the remaining six (6) come from the Accounting Department. The results of the study shows that the faculty of the College of management have been provided with efficient and effective. This conclusion has been arrived simply because the results clearly shows that the teacher were provided with adequate trainings which would their needs as educators. These have been provided by the OESCE and outside institutions. Furthermore, the results showed that the trainings were very much applicable to the needs of the teachers. These trainings were able to provide the necessary knowledge and skills which the teacher needs in his or her field of specialization. Thus, the researchers have arrived with the conclusion that the trainings provided to the CM Faculty were efficient and effective.
Research Paper (Mgt 200-Management Research). -- [Iloilo City] : University of the Philippines in the Visayas - College of Management, March 1997.